Primarily Assessment of Mamuniyat Formation Sandstones for Glass Industry, Idri Area, SW Libya - Fares , Fares F. (Scientific Journal of University of Benghazi, 2020)
In this study, we conducted a geochemical assessment of the Mamuniyat Formation sandstones for glass industry in Idri area, SW Libya. Eighteen sand stone samples were subjected to the inductively coupled plasma-mass spectrometry (ICP-MS) technique. The chemical analysis data suggests the Mamuniyat Formation sandstones in the study area are suitable for three common types of glass industry (i.e. sod - lime glasses, lead glasses and borosilicate or heat resistant glasses).